Estudio comparado del esqueleto caudal en peces characoideos de la República Argentina : II. Familia Characidae - Miquelarena, Amalia María (1982)
This paper is part of a comparative study of the caudal skeleton in South American Characoidei. Following the Monod’s system (1967, 1968), the morphology of the urophoral complex is studied in thirty two species of the family Characidae. Possible phylogenetic relationships between the studied entities are suggested. The diagnostic value on: a familiar and even generical level, of the urophoral complexe is confirmed in a high number of South American species. These are arranged according to Gery’s classification (1972).